2004
DOI: 10.4067/s0717-71782004000100010
|View full text |Cite
|
Sign up to set email alerts
|

El loco Concholepas concholepas (Bruguière, 1789) (Mollusca: Gastropoda: Muricidae) como recurso durante el Holoceno Temprano-Medio en Los Vilos, Chile central

Abstract: RESUMEN.Se estudió la abundancia relativa del loco, Concholepas concholepas, y las causas posibles de su variabilidad en los conchales culturales más antiguos del Holoceno Temprano-Medio del litoral de Los Vilos (31º55'S, 71º32'W). Las muestras se obtuvieron en excavaciones arqueológicas de cinco sitios y se dataron con C 14 : Punta Purgatorio (LV079: 10.040 ± 70 años antes del presente, a.a.p.), Caleta Ñagué (LV098: 10.120 ± 80 a.a.p.), Dunas de Agua Amarilla (LV166: 6.700 ± 60 a.a.p.), Borde Norte de Quebrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
0
5
0
3
Order By: Relevance
“…30-331S) have yielded mixed results (Jerardino et al, 1992;Baez et al, 2004). On the one hand, Jerardino et al (1992) reported a marked decline in the shell size of C. concholepas observed during an $8000 years period of occupation, from 9000 to 1300 years BP at the Curaumilla site (331S).…”
Section: The Prehistoric Phase Of Harvestingmentioning
confidence: 97%
See 3 more Smart Citations
“…30-331S) have yielded mixed results (Jerardino et al, 1992;Baez et al, 2004). On the one hand, Jerardino et al (1992) reported a marked decline in the shell size of C. concholepas observed during an $8000 years period of occupation, from 9000 to 1300 years BP at the Curaumilla site (331S).…”
Section: The Prehistoric Phase Of Harvestingmentioning
confidence: 97%
“…On the one hand, Jerardino et al (1992) reported a marked decline in the shell size of C. concholepas observed during an $8000 years period of occupation, from 9000 to 1300 years BP at the Curaumilla site (331S). However, Baez et al (2004) presented data showing no decline in the shell size of C. concholepas at Los Vilos site (ca 321S) during a ca 4500 years occupation period (9200-3900 years BP), during the mid-Holocene. These results suggest that human impacts were spatially variable and/or the resilience of rocky intertidal communities to human impacts was variable along the coast.…”
Section: The Prehistoric Phase Of Harvestingmentioning
confidence: 99%
See 2 more Smart Citations
“…El loco (Concholepas concholepas) se distribuye desde la costa central de Perú a Magallanes (Moreno et al, 1998) siendo extraído por las comunidades litorales desde el Holoceno temprano (Báez et al, 2004;Rivadeneira et al, 2010). A fines de la década del 70's y comienzos de los 80's, los desembarques aumentaron (incentivos por demanda y precio) disminuyendo drásticamente poco después de El Niño 82-83 en la zona norte (Regiones I-III), segunda mitad de la década (Regiones la IV y X), y a mediados de los 90's al sur (B. Yannicelli, com.…”
Section: Concholepas Concholepas Y Variabilidad Ambientalunclassified